Stonemasonry skills development: two case studies of historic buildings in Scotland. Issue 3 (11th July 2016) - McGibbon, Scott; Abdel-Wahab, Mohamed
Abstract : Purpose: – Scotland's built heritage (pre-1919 building stock) is exhibiting varying levels of disrepair, in particular for stonemasonry works, despite the government's on-going efforts for promoting higher standards of repair and maintenance (R & M) of historic buildings. The purpose of this paper is to examine the problems associated with the R & M of historic buildings. Design/methodology/approach: – Two case studies (Projects A and B) exhibiting critical disrepair are reported. Site surveying was carried-out on both projects, to identify site features and R & M problems along with proposed solutions drawing on the lead author's extensive industry experience as a stonemasonry consultant. Three semi-structured interviews were conducted with professionals involved in each project to elicit views on the challenges faced. Additionally, three industry experts were interviewed to provide a wider perspective of the R & M challenges facing historic buildings. Findings: – Neglect and poor practice resulted in both projects becoming more challenging and expensive than they needed to be, which was attributed to generic and advanced skills 6deficiencies of the workforce. There is an urgent need for a multi-disciplinary approach to the development of a method statement for R & M, drawing on the expertise of professionals and contractors, particularly when specifying repairs to structural elements. Originality/value: – This paper has provided original and valuable information on R & M problems, highlighting the importance of continued investment in skills development for historic building R & M to enhance existing current training provision and practice. There is a need for further similar project-based data to inform skills development strategies for the R & M of historic buildings as well as enhancing existing qualification frameworks.